Optimization of cogeneration systems under alternative performance criteria - Yilmaz, T (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
In this study, a performance analysis based on alternative performance criteria has been performed for a reversible Carnot cycle, modified for cogeneration, with external irreversibilities. The optimum values of the design parameters of the cogeneration cycle were determined for different criteria. In this context, the effects of design parameters on the exergetic performance are investigated, and the results are discussed. The obtained results may guide towards a more realistic criterion for actual cogeneration plants. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: performance criteria; performance optimization; cogeneration cycle; reversible Carnot; Thermodynamics; Energy & Fuels; Mechanics